Reformasi Pendidikan Islam Di Pakistan: Ketegangan Antara Konservatisme Agama Dan Tuntutan Global - delvia, Melda; Dede Rosyada; Muhammad Zalnur; Titi Sartini; Elijonnahdi (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to provide a comprehensive analysis of the dual structure of Islamic education in Pakistan, encompassing formal education integrated into the national system through the Islamiyat curriculum and traditional education conducted in madrasas based on the classical Dars-e-Nizami syllabus. The research focuses on examining the relationship between government educational policies, the dynamics of traditional madrasas, and the challenges of integrating Islamic values with the demands of modernity. A qualitative descriptive approach was employed through an extensive literature review of official documents, scholarly articles, and publications from international organizations. The findings reveal that reforms such as the Single National Curriculum (SNC) and madrasa regulation represent significant policy initiatives; however, their implementation is hindered by ideological resistance, structural constraints, and the lack of participatory approaches. Islamic education in Pakistan remains in tension between religious conservatism and global imperatives, highlighting the need for inclusive, transformative policies built on multi-stakeholder collaboration. These findings have implications for the development of adaptive, moderate, and contextually relevant models of Islamic education in other Muslim-majority countries